Benthix VR: A Virtual Reality Simulation Application to Preserve Traditional Benthik Game - Setiawan, Abas; Nugraha, Alvin Satria; Haryanto, Hanny; Gamayanto, Indra (ComTech: Computer, Mathematics and Engineering Applications, 2017)
This research aimed to preserve Benthik traditional game using Benthix VR. Benthix VR used the Virtual Reality Interface Design (VRID) development model. The development phase of the VRID model started from High Level to Low-Level phase. The High-Level Design (HLD) phase consisted of identifying data elements and multiple objects, and modeling component objects. The output from the HLD phase would be input to the Low-Level Design (LLD) phase. The LLD phase was a phase of repetition and fine-tunes from the modeling of several component objects thoroughly. Testing of Benthix VR was conducted on 34 respondents with five assessment aspects. Those were enjoyment, realism, interactivity, usability, and impact. The average result of the questionnaire assessment of all aspects is 3,18824. These results indicate that users feel that Benthix VR is comfortable, realistic, interactive, and fascinating. Moreover, they are also interested in playing Benthik in the real world after using the application.